Mean Leaf Angles Affect Irrigation Efficiency and Physiological Responses of Tropical Species Seedling - Delgado, Luiz Gustavo Martinelli [UNESP]; Silva, Richardson Barbosa Gomes da [UNESP]; Gabira, Mônica Moreno; Rodrigues, Angélica Lino [UNESP]; Simões, Danilo [UNESP]; Almeida, Luiz Fernando Rolim de [UNESP]; Silva, Magali Ribeiro da [UNESP] (MDPI, 2022)
In forest nurseries, irrigation management becomes more complex as different seedlings of tropical species, with different architectures, are grown close to each other. In this context, there are gaps in knowledge about the physiological responses of species with different mean leaf angles when subjected to different irrigation depths. Thus, this work aimed to analyze whether mean leaf angles affect irrigation efficiency and, consequently, physiological responses of tree seedlings. Six species with different mean leaf angles were submitted to three irrigation depths (6, 9, and 12 mm) applied daily by micro-sprinklers in a completely randomized design in a split plot scheme. The following variables were evaluated: leaf water potential, stomatal conductance, relative water content in the leaf, daily transpiration, leaching fraction, and total dry mass. In tree species seedlings with positive mean leaf angles, smaller irrigation depths are already able to increase leaf water potential, stomatal conductance, leaf relative water content, and transpiration efficiency. In contrast, when the mean leaf angles are negative, it is necessary to apply larger irrigation depths so that seedling physiological responses do not reduce the production of total dry mass.
Keywords: leaf water potential; seedling architecture; stomatal conductance; transpiration